MANAJEMEN PEMBELAJARAN KODING BERBASIS BLOK WARNA UNPLUGGED UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR LOGIS SISWA SD - Dhita Annisa Fauzia; Eva Dianawati Wasliman; Sri Handayani (STKIP Subang, 2025)
This study aims to analyze the implementation of color-block unplugged coding instruction management in enhancing elementary school students’ logical thinking skills. This research employed a qualitative descriptive approach with fifth-grade students as the research subjects. Coding instruction was carried out through unplugged activities using color-coded cards and command blocks that represent algorithmic concepts such as sequencing, conditions, and loops. This model allows students to understand programming logic without relying on digital devices. Data were collected through observations, interviews, and pre- and post-tests of logical thinking skills. The results indicate that well-structured instructional management, the use of engaging and concrete color-block media, and students’ active participation in problem-solving activities significantly improved their logical thinking abilities. In addition, students demonstrated increased learning motivation, confidence, and collaborative skills. Therefore, color-block unplugged coding can serve as an innovative alternative for developing computational literacy in elementary education.